The Role of Components of the Lymphoreticular System in Transmissible Spongiform Encephalopathy Pathogenesis and Neuroinvasion - Spinner, D.S.; Ye, X.; Carp, R.I.; Kascsak, R.J. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
The transmissible spongiform encephalopathies (TSEs), or prion diseases, are a group of neurodegenerative disorders that affect a variety of mammalian species. These diseases include scrapie in sheep, bovine spongiform encephalopathy (BSE) in cattle, chronic wasting disease (CWD) in elk and deer, and Creutzfeldt-Jakob disease (CJD) in humans. Recently, the transmission of BSE to humans has led to the formation of a new class of human TSE known as new variant CJD (nvCJD). Indicative of TSEs in vivo is the presence of an abnormal conformer of the naturally occurring host protein PrPC, referred to as PrPSc. Expression of PrPC by a potential host is an absolute requirement for a TSE infection to progress to clinical disease. While TSE agents ultimately affect the brain, for optimal pathogenesis and neuroinvasion kinetics most strains require functionally intact lymphoid organs. Accordingly, a majority of the data compiled to date on TSEs indicates that bolstering lymphoreticular function potentiates the ability of most agent strains to induce symptomatology in a given host. Attenuation of such functioning by various means, conversely, can severely diminish or, for some strains of agent, completely ablate pathogenesis and neuroinvasion. In this review we examine the cellular and physiological bases for these findings and explore possible underlying mechanisms of TSE pathogenesis. In addition, we examine new lines of research required to complete the puzzle of how TSEs utilize cells of the lymphoreticular system to their advantage and complete the neuroinvasion process.
Keywords: transmissible spongiform encephalopathies